STATISTICAL ANALYSIS OF LABOR MARKET EFFICIENCY IN THE WORLD COUNTRIES - E. Dolgikh; T. Pershina (Вестник университета)
The study of the labor market allows to determine the main directions of development of the country’s economy, which largely depends on a set of indicators. The article gives detailed characteristics of the components of the labor market efficiency, proposed by the World economic forum in the Report on global competitiveness. Russia’s positions among the world countries according to the importance of the efficiency of the labor market and their dynamics for the period from 2013 to 2017 have been considered. Multidimensional grouping of the world countries according to ten components has been performed, and detailed characteristics of the selected clusters has been given.